Solution to the unit commitment and economic dispatch problem of Luzon grid to optimize NPC and Meralco bilateral contracts with independent power producers - Basa, Joris Noel P. (2004)
The price of electricity is dependent on the costs of operation of the power system. On the generation sector, production costs are mostly in the form of fuel costs for the operation of the generators. Fuel costs alone would oftentimes comprise about eighty to ninety percent of the total operation cost of generators. These fuel costs are related to the power generated and are directly passed on the consumers. Thus management of the generators is needed for economic purposes. Minimization of costs is necessary so as to keep prices as low as possible. Minimization of costs or optimization can be done through economic load dispatch alongside unit commitment. Use of these concepts should be done in order to obtain a desirable condition. That is, obtaining a reliable scheduling for generator operations that would generate minimal costs. The power system of the Philippines is to undergo deregulation. With deregulation, participants would be allowed to undergo bilateral agreements. To maintain optimization in a deregulated market, economic load dispatch and unit commitment would be done taking into consideration the effects of the terms stated within the bilateral contracts. Based upon the agreement between two parties, basically between the generator and the consumer, the terms and conditions stated in a bilateral contract would affect the costs in the operation of the generator. Though the system in the Philippines is to be deregulated, regulation would still be needed in terms of supervising terms of bilateral contracts. Since the bilateral contracts currently in action are those between NPC, Meralco and different independent power producers (IPP's) the effects are directly reflected on the consumers billing thus the need for a reliable way of handling generators with bilateral contracts.